(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper investigates the use of Hausa-English Code-switching in Hausa Islamic preachings in Northern Nigeria. The objectives of this research are to identify instances of code-switching in Hausa Islamic preachings and to analyze its type. The study employs functionalist view of Discourse analysis as the theoretical frame work in the analysis of data and ethnography of communication method for the data collection. The findings of the research show that, code-switching in Islamic preaching is a conscious and unconscious behavior and intra-sentential switching is more commonly used than any other type of switching. It also reveals that the preachers switch to the two codes for different functions such as: clarification, situational, attraction of attention and addressing audience, similarly the research showed the existence of inter-sentential, intra-sentential and tag-(types of code-switching) in the Islamic preachings.